Designing Lets Listen Multimedia CD for Listening Comprehension - Wulanjani, Arum Nisma (English Language and Literature International Conference (ELLiC) Proceedings, 2017)
Teaching listening in a language laboratory can be a beneficial or even a challenge for a teacher, especially in elementary school. It is beneficial since the laboratory is equipped by sophisticated aids to support the listening learning process. On the other hand, choosing an appropriate material which can be supported by the aids and meet with students need is the challenge must be aware by the teacher. This study proposes an answer for the challenge. This study describes an interactive multimedia CD development which is intended for listening learning process especially for fifth grade elementary students.Design-based research is used in this study. The steps proposed by Thiagarajan, Semmel, & Semmel (1974) are the basis of conducting the study. Some adjusted stages were conducted such as the define stage, design stage, and develop stage. The multimedia CD was designed interactively so that the students can involve actively in the listening learning process, since it also provides interactive feedback. The existence of the feedback would make the learning process more successful because the responses from the students are also noticed. Some suggestion and revison from some experts completed the process of the development. Based on the experts analysis, Lets Listen multimedia CD has met the criteria to be a teaching material for listening comprehension especially for fifth graders. Lets Listen multimedia CD has an advantage for its use, it allows the students to have student-centered learning and self assessment which can lead them into independent learning.